SLAP II REPAIR - NEW TECHNIQUES, COMPLICATIONS AND CLINICAL OUTCOMES - Michalina Adamczyk,; Aleksandra Lisowska,; Pola Sitek,; Dariusz Szołtys,; Karolina Zygoń-Komendarczyk,; Katarzyna Oberska,; Sandra Olewińska,; Tola Kotkiewicz,; Hanna Grygorcewicz,; Yelyzaveta Petrenko, (International Journal of Innovative Technologies in Social Science, 2026)
Superior labrum anterior to posterior (SLAP) type II lesions represent a clinically significant source of shoulder pain and dysfunction, particularly in young athletes and individuals engaged in repetitive overhead activities. Detachment of the superior labrum and biceps anchor disrupts glenohumeral biomechanics, potentially leading to instability, mechanical symptoms and impaired athletic performance. Although arthroscopic repair remains the standard surgical approach, optimal management strategies continue to evolve in response to variable return-to-sport rates and procedure-related complications observed with traditional techniques.Contemporary surgical concepts emphasize anatomic restoration of the labral-biceps complex while minimizing implant-related morbidity. Innovations such as anatomic double-pulley constructs aim to distribute fixation forces more evenly and reduce peel-back stress during overhead motion. Knotless anchor systems and low-profile suture-tape constructs have been developed to eliminate intra-articular knots, decrease chondral irritation and facilitate smoother rehabilitation. In parallel, single-portal approaches seek to reduce soft-tissue disruption without compromising biomechanical stability. For selected patients particularly those with degenerative labral tissue or advanced age, biceps-based alternatives such as tenodesis provide a viable strategy with comparable functional outcomes and potentially earlier pain relief.Early and mid-term results of these contemporary techniques demonstrate meaningful improvements in pain, shoulder function and patient satisfaction. Nevertheless, postoperative stiffness, persistent discomfort and incomplete return to high-demand activity remain clinically relevant challenges. Careful patient selection, meticulous surgical execution and individualized rehabilitation protocols are essential for optimizing outcomes. Further long-term, high-quality studies are required to refine treatment algorithms and establish durable, evidence-based recommendations.